Influence of surface geometry and the cam-post mechanism on the kinematics of total knee replacement. - Pandit, H; Ward, T; Hollinghurst, D; Beard, D; Gill, H; Thomas, N; Murray, D (2005)
Abnormal sagittal kinematics after total knee replacement (TKR) can adversely affect functional outcome. Two important determinants of knee kinematics are component geometry and the presence or absence of a posterior-stabilising mechanism (cam-post). We investigated the influence of these variables by comparing the kinematics of a TKR with a polyradial femur with a single radius design, both with and without a cam-post mechanism. We assessed 55 patients, subdivided into four groups, who had undergone a TKR one year earlier by using an established fluoroscopy protocol in order to examine their kinematics in vivo. The kinematic profile was obtained by measuring the patellar tendon angle through the functional knee flexion range (0 degrees to 90 degrees ) and the results compared with 14 normal knees. All designs of TKR had abnormal sagittal kinematics compared with the normal knee. There was a significant (p < 0.05) difference between those of the two TKRs near to full extension. The presence of the cam-post mechanism did not influence the kinematics for either TKR design. These differences suggest that surface geometry is a stronger determinant of kinematics than the presence or absence of a cam-post mechanism for these two designs. This may be because the cam-post mechanism is ineffective.